2014
DOI: 10.4149/av_2014_03_292
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in cultured murine neurons infected with equid herpesvirus 1

Abstract: Summary. -In this study we investigated the relationship of equid herpesvirus 1 (EHV-1) infection to autophagy in primary culture of murine neurons. Infection with both Jan-E and Rac-H strains of EHV-1 resulted in the formation of autophagosomes in the cytoplasm during early stages of infection, while in late stages of infection autophagosomes were mainly concentrated around the nucleus what suggests the induction of nuclear envelope-derived autophagy (NEDA). No significant effect of an authophagy inhibitor-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…EHV-1 is a pathogen that causes respiratory diseases, abortion, and neurological disorders in horses. EHV-1 belongs to the Alpaherpesvirinae subfamily and has a double-stranded DNA genome (Cymerys et al, 2014). EHV-1 infection in the primary culture of murine neurons induces autophagy (Cymerys et al, 2014).…”
Section: Other Animal Viruses and Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…EHV-1 is a pathogen that causes respiratory diseases, abortion, and neurological disorders in horses. EHV-1 belongs to the Alpaherpesvirinae subfamily and has a double-stranded DNA genome (Cymerys et al, 2014). EHV-1 infection in the primary culture of murine neurons induces autophagy (Cymerys et al, 2014).…”
Section: Other Animal Viruses and Autophagymentioning
confidence: 99%
“…EHV-1 belongs to the Alpaherpesvirinae subfamily and has a double-stranded DNA genome (Cymerys et al, 2014). EHV-1 infection in the primary culture of murine neurons induces autophagy (Cymerys et al, 2014). However, EHV-1-induced autophagy has no effect on EHV-1 replication (Cymerys et al, 2014).…”
Section: Other Animal Viruses and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Alexander et al found that HSV-1-induced autophagy has no effect on viral replication, that HSV-1 ICP34.5-deleted mutants cause autophagy, and that inhibition of HSV-1 ICP34.5-deleted mutant-induced autophagy has no effect on viral replication [ 92 ]. The early stages of EHV-1 infection of cultured murine neurons causes autophagy but has no effect on EHV-1 replication [ 93 ]. This seemingly contradictory outcome has a reasonable explanation: on the one hand, other forms of autophagy in addition to xenophagy may be involved in immune regulation, whereas on the other hand, other factors initiated by innate immune and acquired immunity may be involved in immune regulation.…”
Section: The Roles Of Apoptosis Autophagy and Necroptosis In Alpha-hmentioning
confidence: 99%
“…We also observed an autophagy induction during infection of primary murine neurons with both Jan-E and Rac-H strains of EHV-1. However, chloroquine (autophagy inhibitor) did not affect the level of replication of the virus, quantified with real-time PCR method (Cymerys et al 2014 ). These results led us to further studies on kinetics of EHV-1 replication during long-term neuronal infection and to examine the effects of the neuronal passage on EHV-1 neurovirulence.…”
Section: Introductionmentioning
confidence: 99%